Experiences of Math Pre-service Teacher in Microteaching - Baluyos, Genelyn R.; Insong, Ralph Joseph G.; Jumawan Jr., Nelson A.; Lumayag, Junjie B. (PT ARRUS Intelektual Indonesia, 2024)
In the rise of the digital age, microteaching is an excellent factor in education. Education usually uses microteaching as their teaching method because this study described the experiences encountered by Math preservice teachers in microteaching. This study utilized the qualitative approach using phenomenological design. The study participants included ten math preservice teachers who underwent microteaching for the school year 2021-2022 and were selected through purposive sampling. The researcher used a researcher-made interview guide to elicit data from the participants using Moustakas' structured method of data analysis. Results revealed four themes: 1.) Mixed Emotions in Preparing for Microteaching; 2.) Efficiency of Learning Materials for Microteaching; 3.) Technical Difficulties in Actual Teaching 4.) Realizing One's Ability in Teaching. This study concluded that microteaching helps math preservice teachers in their teaching careers and develops abilities and strategies that they acquire to enable them to become effective teachers. However, they also encountered negative experiences in microteaching. The math preservice teacher developed negative emotions in preparing for microteaching and experienced technical difficulties in the actual demonstration. The study recommends that teachers explore other microteaching techniques in advance programming for editing digital materials and platforms, including Office 365 and Google Suite, and let the math preservice teacher with no laptops and unstable internet connection use the Media Resource Laboratory. Future researchers must conduct another study exploring the factors of developing negative and positive reactions in microteaching.